2010
DOI: 10.3846/jbem.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Systems in Madeira Island Largest Firms: Evidence on the Balanced Scorecard Usage

Abstract: Abstract. This paper describes the findings of an exploratory study on the use of management control systems in Madeira Island providing evidence on the Balanced Scorecard (BSC) usage. Empirical data collected illustrates the degree of BSC usage at the Island's biggest corporations and provides response to the research questions. The findings reveal remarkable differences concerning management control systems' use across corporations in the study and previous research reports from other regions. Finally, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In fact, Hypothesis 2 confirmed that the interactive use of the employee performance appraisal system (Figure ) leads to greater perceived effectiveness of the control in environments characterized by high environmental uncertainty rather than in more stable environments, where a diagnostic use is preferred. Following Curado and Manica (), this view is certainly valid for the system of individual performance appraisal and offers insights for a deeper analysis of the system for non‐financial performance measurement (Figure (A) and (B)). Contrary to what the theory implies, the interactive use of budgeting in situations of high environmental uncertainty leads to a worsening of the perceived PMS's effectiveness, a result that can be associated with the particular sector being investigated, as the health sector has introduced budgeting as a mechanism of economic planning more recently than have for‐profit organizations; thus, the level of interaction in its use is still low (Anessi‐Pessina and Cantù, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Hypothesis 2 confirmed that the interactive use of the employee performance appraisal system (Figure ) leads to greater perceived effectiveness of the control in environments characterized by high environmental uncertainty rather than in more stable environments, where a diagnostic use is preferred. Following Curado and Manica (), this view is certainly valid for the system of individual performance appraisal and offers insights for a deeper analysis of the system for non‐financial performance measurement (Figure (A) and (B)). Contrary to what the theory implies, the interactive use of budgeting in situations of high environmental uncertainty leads to a worsening of the perceived PMS's effectiveness, a result that can be associated with the particular sector being investigated, as the health sector has introduced budgeting as a mechanism of economic planning more recently than have for‐profit organizations; thus, the level of interaction in its use is still low (Anessi‐Pessina and Cantù, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies made in several countries have very diverse Balanced Scorecard utilization rates, namely: 65% for companies in Bahrain (Juhmani, 2007); 53% for Swedish companies in various industries (Kraus and Lind, 2010); 48% for Brazilian companies (Amorim and Machado, 2015); 35% for the US public sector (Crabtree and DeBusk, 2008); 24% for companies rated as the best to work for in Portugal (Machado and Simplício, 2016); 19% for large Portuguese companies (Quesado and Rodrigues, 2009); 19% for hotels located in Portugal (Nunes and Machado, 2014); 10% for companies in Madeira (Curado and Manica, 2010); 5% for small and medium-sized industrial companies in Portugal (Machado, 2013). On the other hand, empirical studies on the use of the Tableau de Bord are very scarce.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Consequently, some authors (e.g. Fleisher, Mahaffi 1997;Ottoboni et al 2002;Curado, Manica 2010) have been pointing out several limitations to the BSC, such as: (1) it preserves the emphasis on financial results by submitting all measures to financial objectives; (2) its practical implementation "takes a considerable amount of time (up to 30 months) to design and implement as a strategic management system" (Fleisher, Mahaffi 1997); (3) its formulation may depend on the relative negotiation power of different groups; (4) other stakeholders, not previously considered in the four perspectives, may arise; (5) it does not explore the interrelationships between partial indicators and the organization's overall performance, such that it is possible to observe, simultaneously, a set of values presenting satisfaction and other set of values presenting dissatisfaction; (6) the analysis may be limited by "interpretation effects"; and (7) raises doubts on the way that relative weights are chosen to balance the evaluation criteria (for a categorized list of BSC limitations, see Curado, Manica 2010).…”
Section: General and Specific Limitations Of The Bsc Applicationsmentioning
confidence: 99%
“…Present-day economic thinking assumes that performance evaluation is a key element for the promotion of improvement initiatives (Urbonavičius, Ivanauskas 2005;Strandskov 2006;Zinkevičiūte 2007;Santos et al 2008;Acar, Zehir 2010;Curado, Manica 2010). As stated by Santos et al (2008), "formal or informal performance measurement is common practice in most organizations and it is well established that this plays a critical role in signalling the level of success in achieving objectives and identifying where improvement efforts are required".…”
Section: Introductionmentioning
confidence: 99%